Formalization, Discretion, and Trust on Public Procurement Market - Chrisidu-Budnik, Agnieszka (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
A public contract is a contract to which the parties are the contracting authority and the contractor. The public procurement process is a legal category of a dynamic nature made up of three stages: preparation, award and fulfilment of the public contract. This is a highly formalized legal category. Formalizing has the objective of ensuring economic viability of the whole of the public procurement system, its transparency and integrity of the participants of the public procurement markets. At the same time, an excessively high degree of formalization may prove to be harmful and ineffective for the achievement of these objectives, because it limits the flexibility of the contracting entity’s and contractor’s activities. Therefore, being aware of the existence of the dilemma of formalization, the lawmakers face the need to balance these two groups of values. The compromise understood in this way is expressed by the presence in the public procurement law of a certain degree of discretion that facilitates and makes the flow of information between the parties to the agreement more effective and simultaneously creates space for the emergence of a relationship of trust between the contracting authority’s and the contractor’s institutions. The article is limited to the examination of the extent of discretion at the stage of preparation and award (conclusion) of the contract.
Keywords: public contract; discretion; trust; credibility